Journal of Badiou Studies 5 Architheater (Punctum Books, 2017)
The fifth volume of the Journal of Badiou Studies, "Architheater," energized by the publication of Badiou's Rhapsodie pour le théâtre (2014), knits together distinguished approaches to artistic production engaging with the work of Alain Badiou: 'Engaging' here means articulated positions that include, imply, or criticize the Badiouiesque corpus. The issue does not therefore seek to implement Badiou's philosophical insights in interpretations of art or of aesthetics, but rather to take Badiou's philosophy as a center of convergence-nexus of a plethora of philosophical positions that include artistic production as a central element of their structure. Thematically, the volume limits its discussion to "a two" of architecture and theater, thinking their overlapping, juxtaposition, and respective generative capacities. JBS 5 suggests superimposing these two "media" and posing them at the center of the volume for several reasons: Politically, both theater and architecture actively engage in the life of the polis, they effectually and factually demand the participation of collective and material actors. Poietically, both media manifest a comprehensive form of artistic production, that is to say they both include elements and organs (actors, designers, lighting-specialists, engineers, planners, executives, actors, dancers, etc.) that are required as collaborators in the realization of the piece. The Architect, on the one hand, and the Theater maker, on the other, both produce what could be defined as a world, or, in Badiou's terms, a formation of a subject